(untitled) (Journal of Intellectual Property Rights (JIPR), 2024)
The protection of intellectual property rights in the digital realm is of utmost importance, particularly in developing countries like India. This paper conducts a thorough investigation into the role of digital forensics in preserving and enforcing intellectual property rights, specifically within the Indian context. Through an extensive review of relevant literature, we identify gaps in current research and propose a comprehensive methodology for examining and addressing intellectual property infringements in the digital domain. The paper incorporates certain examples and cases where digital forensics may be used to counter infringement. By exploring the intersection of digital forensics and intellectual property rights in India, this study contributes valuable insights to the existing body of knowledge, offering practical implications for policymakers, law enforcement agencies, and intellectual property rights holders operating in similar contexts.